Vertebrates - Kardong, Kenneth
Includes bibliographical references and indexes.; Retaining his unique emphasis on function and evolution of vertebrates, complete anatomical detail, and excellent pedagogy, author Kenneth Kardong includes a substantial amount of new, beautifully-illustrated art and updated narrative in this new edition. This one-semester text is designed for your upper-level majors course.